Brazil and Uruguay white hegemony and Afro-descendant resistance - Vinícius, Paulo (2024)
This article discusses the experiences of Brazil and Uruguay with regard to relations between Afro-descendants and whites, focusing on black resistence. Racism defined the structure of inequalities in both countries, with access to resources and power, both material and symbolic, being very different for whites and Afro-descendants. The article aims to show the coincidences and particularities of the hierarchies based on the racialization of Afro-descendants in both Latin American societies. From a critical and historical perspective, it addresses the origins of colonization and slavery; Afro-descendant activism in both countries and its results; the transformations that occurred in the 1980s and 1990s and arrives at a current assessment. The discussion led to an analysis of the changes in recent decades and an assessment of the inclusion of Afro-descendants and whites in politics and power structures in both countries. The complex historical processes analysed from a comparative perspective presents important differences, but as the same time, many similarities especially when analyzed over prolonged periods. Black movements in both countries, with positive results in policies to promote equality, have confronted the historical processes that have acted and continue to act to racialize societies and maintain spaces of power for whites and subalternity for blacks and indigenous people.